Fabrication of Customized Nanogel Carriers From a UV-Triggered Dynamic Self-Assembly Strategy - Bao, Wuren; Lyu, Jieran; Li, Chunlin; Zhang, Jifeng; Sun, Tunan; Wang, Xing; Zhou, Jin; Li, Dawei (Frontiers in Chemistry, 2019)
Recent advances in self-assembled nanogel carriers have allowed precise design of hierarchical structures by a low-cost solution-phase approach. Typically, photochemical strategy on the tailor of morphology and dimension has emerged as a powerful tool, because light-trigger has exceptional advantages of an instant “on/off” function and spatiotemporal precision at arbitrary time. Herein, we report a tunable manipulation of sequentially morphological transition via a “living” thiol-disulfide exchange reaction from a UV-tailored hierarchical self-assembly strategy. By varying the irradiation time, the photochemical method can easily fabricate and guide a series of attractively architectural evolution in dilute aqueous solutions, by which the improving hydrophobicity and sensitive redox-responsiveness endowed these disulfide-linked nanoparticles with remarkable capacities of abundant encapsulation, effective separation, and controlled release of hydrophobic cargoes. Notably, once the exchange reaction is suspended at any point of time by removing the UV lamp, these active sites within the nanogel carriers are instantaneous deactivated and the correspondingly structural transformations are also not conducted any more. However, if the stable inert sites are reactivated as needed by turning on the UV light, the interrupting morphology evolution can continue its previous steps, which may provide a simple and novel approach to fabricating the desired self-assemblies in solutions. With regard to this advanced functionality, various nanogel carriers with customizable structures and properties have been yielded and screened for cancer therapy. Thus, this “living” controlled self-assembled method to program morphology evolution in situ is a universal strategy that will pave novel pathways for creating sequential shape-shifting and size-growing nanostructures and constructing uniform nanoscopic functional entities for advanced bio-applications.